A Whole Farm Analysis of the Implications of Variable Maturity Groups on Harvest Logistics and Net Returns. (1st June 2017) - Martin, B.; Dillon, C.; Mark, T.; Davis, T.
Abstract : A whole farm economic analysis was performed to maximize net returns utilizing variable maturity groups of corn and soybeans over different soil types. Demand for drying and storage equipment throughout harvest was generated based on profit-maximizing combinations of grain types, their respective maturity groups, and yield potential over different topsoil depths. Two marketing strategies were considered: cash and futures contract sales. It was found that drying equipment became a limiting factor in the proposed system. This prevented storage facilities from reaching full capacity and additional grain from capturing value in the futures market.